LABOUR LAW, INDUSTRIAL RELATIONS AND HUMAN RIGHTS IN RECESSIONARY TIMES: THE ITALIAN CASE - Tiraboschi, Michele (Teisė, 2015)
Article 23 of the Universal Declaration of Human Rights reasserts one’s “right to work”: “Everyone has the right to work, to free choice of employment, to just and favourable conditions of work and to protection against unemployment”. [...]